Quality of life was similar in children with congenital diaphragmatic hernia and oesophageal atresia and related to respiratory morbidity. (19th July 2020) - Darmaun, Laura; Lejeune, Stephanie; Drumez, Elodie; Mur, Sebastien; de Langle‐Chevalier, Fanny; Nève, Véronique; Storme, Laurent; Michaud, Laurent; Gottrand, Frederic; Thumerelle, Caroline; Deschildre, Antoine
Abstract: Aim: To assess quality of life (QoL) in children with congenital diaphragmatic hernia (CDH) and to compare it with oesophageal atresia (OA). Methods: A cross‐sectional study in CDH children (≥7 years) was conducted in Lille University Hospital, France, from January 2013 to April 2014. History, lung function (rest, exercise) and Pediatric Quality of Life Inventory questionnaires (PedsQoL 4.0) were collected. Data of OA children were previously published. Results: Fifty‐four CDH patients (male: 53%, median age: 11 years, IQR 9‐14) were compared to 54 OA patients (male: 61%, median age: 13 years, IQR: 11‐15). CDH children had significantly more frequent history of pneumonia (30% vs 13%), exercise limitation (54% vs 35%) and chest deformity (39% vs 11%); 46% had an obstructive pattern and 66% an abnormal cardiopulmonary exercise test. The median PedsQoL total score in children was 81 (IQR 73‐90) in CDH and 81 (IQR 72‐91) in OA ( P = .8). In CDH, duration of neonatal oxygen therapy, hospitalisation for respiratory disease, exercise limitation, inhaled corticosteroids treatment, chest deformity, abnormal cardiopulmonary exercise test and lower forced expiratory volume in one second were significantly associated with lower QoL scores. Conclusion: PedsQoL scores remained satisfactory in CDH children with CDH, with no difference compared to OA. Patients with respiratory morbidity and lung function impairment, who displayed lower scores, should be identified in order to optimise their management in reference centres.